Blastic plasmacytoid dendritic cell neoplasm of the breast: A case report and review of the literature. Issue 19 (14th May 2021) - Lee, Hyo-jae; Park, Hye Mi; Ki, So Yeon; Choi, Yoo-Duk; Yun, Sook Jung; Lim, Hyo Soon
Abstract: Rationale: Blastic plasmacytoid dendritic cell neoplasm (BPDCN) is an uncommon and aggressive hematologic malignancy that arises from plasmacytoid dendritic cells. BPDCN typically presents with skin lesions with or without involvement of lymph nodes, peripheral blood, or bone marrow. However, breast involvement of BPDCN is rare and there has been no report describing the radiologic features of BPDCN within breast parenchyma. Patient concerns: We report a case of a 47-year-old woman who presented with an incidentally detected hypermetabolic breast lesion on PET/CT with concurrent right cheek plaque. Diagnoses: Skin biopsy was performed for the right cheek plaque. Mammography and breast ultrasonography were performed to evaluate the breast lesion. The lesion was depicted as a 2.5 cm sized focal asymmetry on mammogram and an irregular heterogeneous echoic mass within the mammary zone of the right upper outer breast. Core needle biopsy was performed for the breast lesion. Histologic diagnosis of the two lesions was BPDCN. Interventions: The patient was treated with induction and consolidation chemotherapy and received allogenic peripheral blood stem cell transplantation. Outcomes: The patient remains in complete remission state without relapse at 34 months since initial diagnosis. Lessons: This is the first case of BPDCN manifested as a breast parenchymal mass and assessed by diagnostic breast imaging tools (mammography and ultrasonography). This case report is significant for BPDCN within the breast parenchyma and presenting rare radiologic description of BPDCN.